Validação da emotional processing scale (EPS) para adolescentes brasileiros - Laura Rodrigues Vieira (2019)
The Emotional Processing Scale (EPS) is a British scale designed to assess difficulties in emotional processing. The instrument has demonstrated applicability in different contexts, good discrimination between groups and satisfactory psychometric properties. The purpose of this study was to investigate validity evidences of EPS for Brazilian adolescents aged between 13 to 19 years. Two main steps were conducted: the first step investigated the content validity evidences of EPS by members of the target population (N = 10) and by a committee of expert judges (N = 6). Two questionnaires were used for data collection. Qualitative and quantitative data analysis procedures were used (Content Validity Coefficient (CVC) and Kappa de Fleiss). The second step aimed to explore the construct validity evidences based on internal structure and on associations between scores on the scale and other related constructs and variables. EPS Brazilian version’s internal consistency and temporal stability were also assessed. The sample was 482 adolescents (girls: n = 335, 69.5%) aged from 13 to 19 years old (mean = 15.76 years, SD = 1.23). The data were collected from sociodemographic and general health information questionnaire, EPS Brazilian Version, the Self Report Questionnaire (SRQ-20) and the Positive and Negative Affective Scale for Adolescents (EAPN-A). Descriptive (measures of central tendency, dispersion and distribution) and inferential analysis (exploratory analysis by structural equation modeling, Mann-Whitney test, Spearman rank correlation coefficient, coefficients Cronbach's alpha and omega Mc Donald's) were used. The first step resulted in a Brazilian adapted pilot version of EPS that was used to collect data from the second step. Results of the second step demonstrated adequate adjustment of the hypothesized two-factor model. As expected, positive associations were found between: EPS scores and negative affect scores; EPS scores and symptoms of minor psychiatric disorders; as well was found negative association between EPS scores and positive affects scores. As hypothesized, the EPS score was also significantly higher for adolescents with a history of mental disorders. Considering the omega (ω) coefficient, the internal consistency was adequate. In general, internal structure of Brazilian version is promising and the psychometric results were satisfactory. Further psychometric studies are necessary for better exploration of scale proprieties.